2022
DOI: 10.1002/msc.1620
|View full text |Cite
|
Sign up to set email alerts
|

Patient beliefs about who and what influences their hip and knee osteoarthritis symptoms and progression

Abstract: Background: Osteoarthritis management aims to reduce pain and improve function. Many factors affect whether patients follow recommended strategies. Locus of control refers to individual beliefs around who and what influences health. Locus of control is related to the treatment strategies patients prefer. Currently, no studies explore locus of control in non-surgical management of osteoarthritis. Objectives: To explore patients' beliefs about the influences on their osteoarthritis symptoms and disease progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…Our findings support and confirm previous research into the beliefs held by patients and physiotherapists regarding knee OA progression (Bunzli et al., 2019; Kennedy et al., 2022; Wallis et al., 2019). We found that patients and physiotherapists view OA as a wear and tear disease that affects the quality of life and is likely to require surgical input.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings support and confirm previous research into the beliefs held by patients and physiotherapists regarding knee OA progression (Bunzli et al., 2019; Kennedy et al., 2022; Wallis et al., 2019). We found that patients and physiotherapists view OA as a wear and tear disease that affects the quality of life and is likely to require surgical input.…”
Section: Discussionsupporting
confidence: 92%
“…As such, although motivated to engage with health professionals, patients felt a lack of confidence in managing their condition. Moreover, due to commonly held beliefs about exercise causing harm (Bunzli et al., 2019; Kennedy et al., 2022), the patients had previously found engaging in exercise a challenge. In turn, the physiotherapists felt that their current practices were not meeting the needs of all patients, and they were not able to consistently influence the patient's outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with past qualitative research of people with back and knee pain. 17,29,67,112 Thus, our review findings strengthen calls for better shared decision making between health professionals and patients. 20,76,123,101 People with hip pain wanted more information about what treatments were available to them and about the treatments offered to them.…”
Section: Discussionsupporting
confidence: 55%
“…People may have missed opportunities to improve their hip pain and health by avoiding exercise and physical activity; both are recommended treatments for hip pain. 6,64,67,71,85 Social isolation and physical inactivity can also worsen hip pain and magnify its negative impacts. 63,99 Our findings underscore the need for health professionals to explore the emotional and social needs of people living with chronic hip pain.…”
Section: Discussionmentioning
confidence: 99%
“…Poor patient compliance with rehabilitation programs reduces the effectiveness of treatment in individuals with OA. Major barriers to continuity in rehabilitation programs include inappropriate timing, transportation problems, economic inadequacy, and lack of perceived benefit 4 …”
mentioning
confidence: 99%